Integrative taxonomic revision and review of the bioacoustics of the cricket genus Eneoptera (Orthoptera, Gryllidae, Eneopterinae) - Robillard, Tony; Benavides-Lopez, Jose Luis; Tan, Ming Kai; Sperber, Carlos Frankl (Zootaxa, 2026)
We revised the taxonomic and acoustic information on the species of the genus Eneoptera Burmeister, 1838 based on the examination of type specimens and additional material from natural history collections, supplemented by new collections from Colombia, Brazil and French Guiana, and observations from the iNaturalist platform. Our results led us to: (i) revalidate and redescribe Eneoptera caliginosa (Walker, 1869); (ii) propose Eneoptera gracilis Robillard, 2005 as a junior synonym of E. caliginosa (syn. nov.); and (iii) transfer Eneoptera fasciata (Scudder, 1869) to the subfamily Podoscirtinae in the genus Aphonomorphus Rehn, 1903 (comb. nov.). The new observations also allowed us to provide an updated key to the four valid species of Eneoptera.